An Iron Age Horse Bridle Reconstructed: Design, Action and Usability - Laura Bunse (EXARC Journal)
This article presents the reconstruction of an Iron Age horse bridle, which was done at the Lofotr Viking Museum at Borg, Northern Norway, during June 2009. As a part of my master thesis on Iron Age horse gear and horse skeletal remains from Northern Norway, the results from this reconstruction project made an important contribution to the understanding and analysis of the archaeological material.